A DEIXIS ANALYSIS ON LALAYAAN SONG LYRIC OF MINAHASA’S MAENGKET DANCE - Sweetly Tampenawas; Sanerita T. Olii; Jenie Posumah (Universitas Negeri Manado, 2020)
This study aims to identify and describe a Deixis on Lalayan song lyric Minahasa’s Maengket Dance. It is conducted in order to explain what are the deixis and what were the Deixis meaning used on Lalayaan song lyric Minahasa Maengket Dance. In conducting this study, descriptive method is used. The data are collected through interview and observation, the researchers spent many times to interviewing the informant and note the data that relation with this study. The data are analyzed by following the steps of data reduction, data display and drawing conclusion. the result shows that there are 3 types of deixis and be find 37 deixis that use on Lalayaan song of Minahasa Maengket Dance. It is suggested that understand deixis analysis on Lalayaan song Minahasa Maengket dance should be consider in order to get the real meaning that the researcher or speaker exactly meaning.